Multimedia and Critical Thinking on Arabic Guided Writing Learning - Abdul Hakim, Muhammad Kamal bin (IAIN Samarinda, 2019)
The aims of study was to determine the effect of multimedia through film and digital games with pictorial stories in groups of students who have high and low critical thinking patterns on guided writing learning activities in the Arabic Language Education Study Program, Jakarta State University. The study was conducted on the third semester students of the 2018/2019 school year with a total sample of 44 students, which were divided into two groups: 22 students for the experimental group and 22 students for the control group. The research approach uses quantitative research with a 2x2 factorial experimental method. Data collecting technique used tests for writing instruments and critical thinking instruments. The data analysis technique used two-way ANOVA. The results of two-way analysis are known that there are significant effects of multimedia and critical thinking patterns on learning activities of Arabic workshop writing.